Exogenous Ketone Bodies as Promising Neuroprotective Agents for Developmental Brain Injury - Wood, Thomas R; Stubbs, Brianna J; Juul, Sandra E (Developmental neuroscience, 2019)
Ketone bodies are a promising area of neuroprotection research that may be ideally suited to the injured newborn. During normal development, the human infant is in significant ketosis for at least the first week of life. Ketone uptake and metabolism is upregulated in the both the fetus and neonate, with ketone bodies providing at least 10% of cerebral metabolic energy requirements, as well as being the preferred precursors for the synthesis of fatty acids and cholesterol. At the same time, ketone bodies have been shown to have multiple neuroprotective effects, including being anticonvulsant, decreasing oxidative stress and inflammation, and epigenetically upregulating the production of neurotrophic factors. While ketogenic diets and exogenous ketosis are largely being investigated in the setting of adult brain injury, the adaptation of the neonate to ketosis suggests that developmental brain injury may be the area most suited to the use of ketones for neuroprotection. Here, we describe the mechanisms by which ketone bodies exert their neuroprotective effects, and how these may translate to benefits within each of the phases of neonatal asphyxial brain injury.